Mal de Meleda: Genetic Haplotype Analysis and Clinicopathological Findings in Cases Originating from the Island of Mljet (Meleda), Croatia - Bakija-Konsuo, Ana; Basta-Juzbašić, Aleksandra; Rudan, Igor; Šitum, Mirna Nardelli-Kovačić, Magdalena; Levanat, Sonja Fischer, Judith; Hohl, Daniel Lončarić, Davorin; Seiwerth, Sven Campbell, Harry (2002)
Background: Mal de Meleda (keratoderma palmoplantaris transgrediens) is an autosomal recessive disorder, first described on the island of Mljet (Meleda), Croatia. The candidate region for the gene responsible for this disorder was found on the chromosome 8qter, and the responsible mutations have recently been identified in 12 Algerian and 7 Croatian families. Objectives: To fully characterize all 12 living cases originating from the original setting of the disease, the island of Mljet, in the light of new findings and using modern diagnostic technology. Patients and Methods: Twelve patients and 37 family members were identified over the period 1998-1999, interviewed and examined. Results: The reconstruction of 8 genealogies suggests a common ancestry of all cases but one. The clinical presentation and pathologic findings of these cases are described in detail and are consistent with previous report. Symptoms and signs were found to be milder in non-manual workers who had applied continuous symptomatic treatment. Blood samples were taken from 8 cases and 16 close relatives for genetic studies. These confirmed a shared haplotype in all cases, but in none of 17 unaffected control individuals, near the marked D8S1751 on chromosome 8. Conclusions: This review characterizes mal de Meleda in its original setting and shows that the sporadic cases found in the regions of medieval trade routes of the Republic of Dubrovnik (Middkle East and Northern Africa) carry the same mutation as the patients from Mljet Island, Croatia.
Projekt MZOS
Projekt MZOS
Projekt MZOS
ENG